2021
DOI: 10.1186/s13756-021-01030-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experience of how chlorhexidine bathing affects the acquisition and incidence of vancomycin-resistant enterococci (VRE) in a medical intensive care unit with VRE endemicity: a prospective interrupted time-series study

Abstract: Background Critically ill patients in intensive care units (ICUs) often acquire opportunistic infections or are colonized by vancomycin-resistant enterococci (VRE), which limits therapeutic options and results in high case-fatality rates. In clinical practice, the beneficial effects of universal chlorhexidine gluconate (CHG) bathing on the control of VRE remain unclear. This study aimed to investigate whether 2% CHG daily bathing reduced the acquisition of VRE in the setting of a medical ICU (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(34 reference statements)
0
2
0
1
Order By: Relevance
“…Chung et al observed a 51.8% reduction in CRAB infection rates after daily chlorhexidine bathing in ICUs with CRAB endemicity ( Chung et al, 2015 ). Other studies also indicated that daily bathing with 2% chlorhexidine gluconate can reduce CRAB cross-transmission among patients in ICUs with high CRAB endemicity ( Hong et al, 2018 ; Metan et al, 2020 ; Suh et al, 2021 ). Moreover, environmental cleaning, isolation, and enhanced contact precautions are also integrated into strategies preventing CRAB cross-transmission among patients in ICUs because of the environmental reservoirs of CRAB.…”
Section: Strategies and Advicementioning
confidence: 99%
“…Chung et al observed a 51.8% reduction in CRAB infection rates after daily chlorhexidine bathing in ICUs with CRAB endemicity ( Chung et al, 2015 ). Other studies also indicated that daily bathing with 2% chlorhexidine gluconate can reduce CRAB cross-transmission among patients in ICUs with high CRAB endemicity ( Hong et al, 2018 ; Metan et al, 2020 ; Suh et al, 2021 ). Moreover, environmental cleaning, isolation, and enhanced contact precautions are also integrated into strategies preventing CRAB cross-transmission among patients in ICUs because of the environmental reservoirs of CRAB.…”
Section: Strategies and Advicementioning
confidence: 99%
“…En su estudio (Suh et al 2021) (Tien et al 2021) muestran que el baño con clorhexidina es capaz de disminuir hasta en un 70% la incidencia de infecciones asociadas a Enterococcus resistentes a la Vancomicina. (Musuuza et al 2019) (Reis et al 2022) (Scheier et al 2021) (Martinez et al 2020) declaran que el uso del baño con clorhexidina en pacientes críticos se relaciona fuertemente con una disminución de las infecciones del torrente sanguíneo.…”
Section: Discussionunclassified
“…Enhanced environmental cleaning methods may be recommended due to documented instances of persistent VRE presence in hospital rooms despite standard cleaning procedures [207,208]. Recent studies have demonstrated that decolonization through the use of chlorhexidine gluconate bathing for patients in Intensive Care Units (ICU) can prevent hospital-acquired infections and reduce the acquisition rate of MDR organisms including VRE [209]; this could be a potentially interesting path to follow for wards characterized by the presence of immunocompromised patients. Published data highlight the possibility of using capsular and cell wall polysaccharides as targets for immunotherapeutic choices.…”
Section: Prevention and Infection Control Strategiesmentioning
confidence: 99%